IgA anti‐epidermal transglutaminase autoantibodies: a sensible and sensitive marker for diagnosis of dermatitis herpetiformis in adult patients. (2nd June 2012) - Borroni, G.; Biagi, F.; Ciocca, O.; Vassallo, C.; Carugno, A.; Cananzi, R.; Campanella, J.; Bianchi, P.I.; Brazzelli, V.; Corazza, G.R.
Abstract Background Dermatitis herpetiformis (DH) is a rare gluten‐sensitive blistering itchy skin disease, strictly related to coeliac disease (CD). Direct immunofluorescence, demonstrating IgA granular deposits localized either in the dermal papillae or along the dermo‐epidermal junction, is currently the gold standard for diagnosis of DH. It has been shown that DH immunocomplexes contain epidermal transglutaminase (eTG) and that sera from patients with DH contain antibodies specifically directed against eTG. Objectives We studied the usefulness of serum eTG antibodies in discriminating between DH, CD and other gastrointestinal and dermatologic diseases. Methods eTG antibodies were tested in 308 adult patients' sera: 44 patients with untreated dermatitis herpetiformis (UDH), 99 patients with untreated coeliac disease (UCD), 70 dermatological controls and 95 gastrointestinal controls. Results In UDH eTG antibody levels were significantly higher than in DH patients on gluten‐free diet, UCD, gastrointestinal controls and dermatological controls. In UCD eTG antibodies strongly correlated with tissue transglutaminase (tTG) antibodies, whereas in UDH no significant correlation was observed. Conclusion Serum IgA eTG antibody determination can efficiently distinguish UDH from other dermatological itchy diseases and is highly sensitive to gluten‐free diet.